2001
DOI: 10.1161/01.cir.103.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Marine n-3 Fatty Acids, Wine Intake, and Heart Rate Variability in Patients Referred for Coronary Angiography

Abstract: The close positive association between n-3 PUFAs and HRV in patients suspected of having ischemic heart disease may indicate a protective effect of n-3 PUFAs against SCD. This may partly explain the reduction in SCD observed in humans with a modest intake of n-3 PUFA. Wine intake was also positively correlated with HRV, but this correlation was no longer significant after controlling for the cellular level of n-3 PUFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 25 publications
8
80
1
4
Order By: Relevance
“…Previous studies have shown a beneficial effect of n-3 fatty acids on HRV in different populations (Christensen et al, 1999(Christensen et al, , 2001a. As in another study with healthy men (Christensen et al, 1999), we observed an increase in HRV in the analysis of men with the lowest SDNN when supplemented with n-3 PUFA.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown a beneficial effect of n-3 fatty acids on HRV in different populations (Christensen et al, 1999(Christensen et al, , 2001a. As in another study with healthy men (Christensen et al, 1999), we observed an increase in HRV in the analysis of men with the lowest SDNN when supplemented with n-3 PUFA.…”
Section: Discussionsupporting
confidence: 85%
“…A positive association between wine and fish consumption was also found in Danish adults (Tjonneland et al, 1999), whereas an Italian study conducted in hospitalized adults failed to find such an association (Chatenoud et al, 2000). In other Danish patients with cardiovascular disease there was a strong association between wine and fish consumption (Christensen et al, 2001). A fish score and the content of n-3 PUFA in adipose tissue (but not wine intake) were independently associated with heart rate variability in these subjects.…”
Section: Discussionmentioning
confidence: 81%
“…There are some additional evidences: subjects drinking red wine showed a high level of ω-6 fatty acids (arachidonic acid 13 %) and ω-3 fatty acids (docosahexaenoic acid 22 %) in phosphatidylethanolamine from erythrocytes (Simonetti P et al, 1995); subjects drinking red wine or ingesting nonalcoholic components present in red wine, showed a general increase in PUFA and a general decrease in ω-6/ω-3 ratio in all platelet phospholipids, with the exception of sphingomyelin; more precisely, the increase in the proportion of ω-6 fatty acids and of ω-3 fatty acids was 10.2 % and 37.5 % in phosphatidylethanolamine, respectively, reflecting a reduction in the ω-6/ω-3 ratio, from 8.08 to 6.47 (Pellegrini N et al, 1996). Also, patients drinking wine showed a high level of ω-3 fatty acids in granulocyte membranes and adipose tissue, and this is related to the diet (Christensen JH et al, 2001). The finding that wine increases ω-3 fatty acids in plasma is relevant because of the numerous publications that have reported biochemical and physiological effects of ω-3 fatty acids in humans and animals that are expected to prevent or ameliorate CHD (de Lorgeril M et al, 1994;Simopoulos AP, 1997;Mori TA et al, 2001).…”
Section: Discussionmentioning
confidence: 99%